NODULES IN SEDIMENTS OF AN ARTIFICIAL RESERVOIR IN THE ALTAI TERRITORY - Shcherbov B.L.; Strakhovenko V.D. (My University, 2006)
Nodules of various compositions, including ferromanganese nodules, have been found in bottom sediments of an artificial reservoir in the central Altai Territory. The nodules were formed in the alkaline environment against the background of a high carbonate content and saturation with oxygen. The rate of nodule growth is no less than 1.7-1.8 mm/yr and the pH value of water varies from 8.0 to 9.7. Fe and Mn contents in soil and loam of the drainage area are lower than the global clarke value, whereas Ca, K, and Na contents are much higher. The main mass of bottom sediments in the reservoir is markedly enriched in Cd, Mg, Mn, Sr, Ni, Cr, Sb, V, and Pb, but they are depleted in Cu, Mo, Zn, and Li, relative to the soil and loam. Elements in ferromanganese nodules are arranged in the following way in terms of the decreasing concentration coefficient: Mn (27) > Ba (13.4) > Co (10.7) > Mo (9.2) > Cd (5.35) > Ni (3.88) > V (3.52) > Cu (3.3) > Fe (3.2) > Sb (2.17) > Sr (2.04) > Pb (1.5) > Zn (1.43) > Cr (1.1) > Li (0.78) > Mg (0.75) > Na (0.69) > K (0.67) > Ca (0.51). The microelemental composition of nodules in the reservoir qualitatively fits the composition of ferromanganese nodules in seas and oceans. However, the contents of major ore elements (Ni, Cu, Co, Zn, Pb, Mo, and V) in ferromanganese nodules from the World Ocean are much higher than in nodules from the examined reservoir. © Pleiades Publishing, Inc. 2006.